Review of the genus Tinissa Walker, 1864 (Lepidoptera, Tineidae, Scardiinae) from China, with description of five new species - Yang, Linlin (Pensoft Publishers, 2012)

(untitled)
Abstract. The genus Tinissa Walker is reviewed for China. Seven species are recognized, of which Tinissa apicimaculata sp. n., Tinissa conchata sp. n., Tinissa connata sp. n.,Tinissa leguminella sp. n. and Tinissa spirella sp. n. are described as new; and Tinissa insularia Robinson, 1976 is newly recorded from China. Photographs of the adults and illustrations of the genitalia are given. A key to all the known Chinese species and a distribution map of Tinissa in China are included.